2011
DOI: 10.1371/journal.pone.0028522
|View full text |Cite
|
Sign up to set email alerts
|

Fast Detection of Unexpected Sound Intensity Decrements as Revealed by Human Evoked Potentials

Abstract: The detection of deviant sounds is a crucial function of the auditory system and is reflected by the automatically elicited mismatch negativity (MMN), an auditory evoked potential at 100 to 250 ms from stimulus onset. It has recently been shown that rarely occurring frequency and location deviants in an oddball paradigm trigger a more negative response than standard sounds at very early latencies in the middle latency response of the human auditory evoked potential. This fast and early ability of the auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 45 publications
3
48
1
Order By: Relevance
“…The PCA-derived frontal component labelled Na was described as having a stronger association with stimulus rarity than target properties; probably rarity can be interchanged with novelty. Intensity effects have been reported for the Na-Pa complex (Althen et al, 2011), yet saturation occurs around 60 dB (Borgmann et al, 2001). Althen et al (2011) posited that the Na represented an early automatic deviant detection process, similar to the conclusion reached by Sonnadara et al (2006) -Cz reference.…”
Section: Accepted Manuscriptmentioning
confidence: 54%
See 3 more Smart Citations
“…The PCA-derived frontal component labelled Na was described as having a stronger association with stimulus rarity than target properties; probably rarity can be interchanged with novelty. Intensity effects have been reported for the Na-Pa complex (Althen et al, 2011), yet saturation occurs around 60 dB (Borgmann et al, 2001). Althen et al (2011) posited that the Na represented an early automatic deviant detection process, similar to the conclusion reached by Sonnadara et al (2006) -Cz reference.…”
Section: Accepted Manuscriptmentioning
confidence: 54%
“…Intensity effects have been reported for the Na-Pa complex (Althen et al, 2011), yet saturation occurs around 60 dB (Borgmann et al, 2001). Althen et al (2011) posited that the Na represented an early automatic deviant detection process, similar to the conclusion reached by Sonnadara et al (2006) -Cz reference. The Na in this study showed an anterior focus and a latency of 29 ms, longer than usually found (Neves et al, 2007), but this…”
Section: Accepted Manuscriptmentioning
confidence: 54%
See 2 more Smart Citations
“…Similar attention-related changes of the ABR have also been shown (Althen, Grimm, & Escera, 2011;Hoormann, Falkenstein, & Hohnsbein, 1994;Galbraith & Arroyo, 1993;Bauer & Bayles, 1990), although some attempts have failed (Hirschhorn & Michie, 1990) and the effect appears to have a limited generality (Hoormann, Falkenstein, & Hohnsbein, 2000). In all, there is indication of attention-related top-down modulation (or suppression) of the auditory neural signal at precortical processing stages, although the results have been inconsistent.…”
Section: Introductionmentioning
confidence: 65%